2019
DOI: 10.3832/ifor2968-012
|View full text |Cite
|
Sign up to set email alerts
|

Role of serotiny on Pinus pinaster Aiton germination and its relation to mother plant age and fire severity

Abstract: Serotiny degree may hypothetically depend on mother plant age and fire severity, and fire severity can strongly affect the regeneration of Pinus pinaster Aiton, which is an obligate seeder species with aerial seed banks stocked in cones showing a certain degree of serotiny. The main objective of this study was to evaluate the effect of serotiny and mother plant age on seed germination of P. pinaster in relation to fire severity. For this purpose, cones were collected in two stands from mother trees of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…We confirmed that the age of the mother tree had a negative effect on seed mass, suggestive of maternal senescence or perhaps of a maternal strategy, resulting in the production of smaller cones containing fewer and heavier seeds at younger age and larger cones with more though smaller seeds at older ages (Cruz et al, 2019 ). In other studies, maternal age has been shown to have a negative effect on offspring performance either directly or mediated by, for example, an effect of maternal age on seed size (Lembicz et al, 2011 ) or germination (Alonso‐Crespo et al, 2020 ).…”
Section: Discussionsupporting
confidence: 77%
“…We confirmed that the age of the mother tree had a negative effect on seed mass, suggestive of maternal senescence or perhaps of a maternal strategy, resulting in the production of smaller cones containing fewer and heavier seeds at younger age and larger cones with more though smaller seeds at older ages (Cruz et al, 2019 ). In other studies, maternal age has been shown to have a negative effect on offspring performance either directly or mediated by, for example, an effect of maternal age on seed size (Lembicz et al, 2011 ) or germination (Alonso‐Crespo et al, 2020 ).…”
Section: Discussionsupporting
confidence: 77%
“…Serotiny is known for its high phenotypic diversity among species, populations, or geographical areas, and it is hypothesized that this variability may not be entirely due only to fire (Tapias et al, 2004;Voltas et al, 2008;Espelta et al, 2011;He et al, 2012;Ne'eman et al, 2012). For example, Martín-Sanz et al (2017) confirmed that water availability had a crucial impact on cone opening and Cruz et al (2019) pointed that serotiny level was higher from young mother trees. Moreover, Pausas (2015a) underlined that most studies focused on differences between fire-related traits whereas trait variance is very important to consider in order to fully understand trait variation mechanisms.…”
Section: Introductionmentioning
confidence: 87%
“…is widely distributed across the western Mediterranean Basin, and fire is a key factor in the regeneration of natural stands [49]. This species can only regenerate from the seed [50,51], and it displays high phenotypic plasticity [52]. Maritime pine has evolutionary adaptations that help it to perpetuate in fire-prone environments [49], but studies in provenance regions in Spain indicate reduced or no serotiny in many provenances in central Spain [25,52].…”
Section: Introductionmentioning
confidence: 99%